2021
DOI: 10.2147/rmhp.s320241
|View full text |Cite
|
Sign up to set email alerts
|

Does Fear of the New Coronavirus Lead to Low-Carbon Behaviors: The Moderating Effect of Outcome Framing

Abstract: Purpose: Air pollution has been found to aggravate the infection and mortality of COVID-19, leading to increasing attention on pro-environmental behaviors. Considering individuals' psychological distance from COVID-19, this research aims to examine the relationship between fear of COVID-19, air pollution concern, and low-carbon behaviors. Methods: Two survey-based studies were conducted in this research. Study 1 consisted of 323 participants and examined the relationships between psychological distance (PD) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 84 publications
(146 reference statements)
1
9
0
Order By: Relevance
“…For example, anxiety due to the perceived threat to climate change and poor environmental health led to adaptive behaviors such as climate activism to reduce the carbon footprint [23,54]. The fear of COVID-19 was found to be positively correlated with lowcarbon footprint behaviors [29][30][31]. Integrating this literature with the cognitive dissonance theory [45] and compensatory consumer behavior model [41], we suggest that this COVID-19-stress will motivate millennials to protect the environment in the hope of improving environmental health and becoming more immune to the health risks associated with the pandemic.…”
Section: Covid-19-stress and Commitment To The Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, anxiety due to the perceived threat to climate change and poor environmental health led to adaptive behaviors such as climate activism to reduce the carbon footprint [23,54]. The fear of COVID-19 was found to be positively correlated with lowcarbon footprint behaviors [29][30][31]. Integrating this literature with the cognitive dissonance theory [45] and compensatory consumer behavior model [41], we suggest that this COVID-19-stress will motivate millennials to protect the environment in the hope of improving environmental health and becoming more immune to the health risks associated with the pandemic.…”
Section: Covid-19-stress and Commitment To The Environmentmentioning
confidence: 99%
“…Several studies have indicated that the fear and stress experienced during the pandemic influenced intentions for sustainable consumption [1][2][3][4][5][29][30][31]. Because millennials are widely known for their environmental concerns/awareness [6][7][8][10][11][12][13]78,80], it is particularly important to explore how they have responded to the environmental crisis amid the pandemic through their consumption habits.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic in Qatar, the study by Hassen et al (2020) observed shifts toward more healthy and sustainable diets. Liu et al (2021) discovered that fear of COVID-19 was positively associated with low-carbon behavior. However, Urban and Kohlová's (2022) study found no uniform effect on the behavioral costs of pro-environmental behaviors, nor on green decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%